Polyimide precursor, polyimide, polyimide film and display device using same
The polyimide precursor, formed by combining specific acid anhydride and diamine structures, addresses the limitations of existing polyimide films by enhancing transparency, heat resistance, low retardation, and mechanical strength, making it suitable for flexible display applications.
Patent Information
- Application Number
- JP2020195319
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Filing Date
- 2020-11-25
- Publication Date
- 2025-04-15
- Estimated Expiration
- 2040-11-25
AI Technical Summary
Existing polyimide films for flexible displays lack sufficient transparency, heat resistance, low retardation properties in the thickness direction, and mechanical strength, which are crucial for high-temperature processing and flexible device applications.
A polyimide precursor is developed by combining a specific acid anhydride structure with an ether group and a diamine monomer containing a fluorene derivative cardo structure, resulting in a polyimide film with improved transparency, heat resistance, low retardation, and mechanical strength.
The resulting polyimide film exhibits excellent transparency, high heat resistance, low retardation in the thickness direction, and mechanical strength suitable for flexible displays, maintaining stable optical properties even at high temperatures.
Smart Images

Figure 0007662327000001 
Figure 0007662327000002 
Figure 0007662327000003
Abstract
Description
[Technical field]
[0001] The present invention relates to a polyimide precursor, a polyimide, a polyimide film, and a display device using the same, which have high transparency, high heat resistance, low retardation, and lift-off properties, and are less susceptible to discoloration and film swelling even at high-temperature steps in the production of the film or display device. [Background technology]
[0002] 2. Description of the Related Art Display devices such as liquid crystal display devices, organic electroluminescence (EL) devices, and touch panels are used as components of various displays, including large displays such as televisions and small displays such as those used in mobile phones, personal computers, and smartphones. For example, an organic EL device is generally produced by forming a thin film transistor (TFT) on a glass substrate, which is a supporting base material, and then forming an electrode, a light-emitting layer, and another electrode on the TFT in that order, and then hermetically sealing them with a glass substrate, a multilayer thin film, etc. Also, a touch panel is constructed by bonding a first glass substrate on which a first electrode is formed and a second glass substrate on which a second electrode is formed via an insulating layer (dielectric layer).
[0003] In other words, these components are laminates in which various functional layers such as TFTs, electrodes, and light-emitting layers are formed on a glass substrate. By replacing this glass substrate with a resin substrate, components using conventional glass substrates can be made thinner, lighter, and more flexible. This is expected to be used to obtain flexible devices such as flexible displays. On the other hand, resins are inferior to glass in terms of dimensional stability, transparency, heat resistance, moisture resistance, and film strength, and various studies are being conducted.
[0004] Polyimide is one of the promising resin substrate materials because of its excellent heat resistance and dimensional stability. In particular, polyimides having fluorine atoms in the polyimide structure (fluorine-containing polyimides) and polyimides having an alicyclic structure (alicyclic polyimides) have excellent transparency and are expected to be applied to flexible devices that require transparency, such as substrates for organic electroluminescence devices, touch panel substrates, and color filter substrates.
[0005] Transparent polyimide substrates for flexible devices can be obtained by forming a transparent polyimide film on a glass substrate, mounting electronic components on the transparent polyimide film, and then peeling off the substrate. Fluorine-containing polyimides have excellent peelability from glass substrates, so they are particularly expected to be used for transparent polyimide substrates.
[0006] For example, Patent Document 1 proposes a polyimide with low thermal expansion and high transparency using a fluorine-containing monomer. However, there is no disclosure about the retardation (Rth) in the thickness direction of the polyimide film. For example, in a substrate for a bottom-emission type organic EL display device, control of Rth is important for the reason of suppressing external light reflection, and in a substrate for a flexible liquid crystal display device, for the reason of controlling contrast when bending. Therefore, when a polyimide film with an uncontrolled Rth is applied to the above substrate, there is a concern that the above-mentioned problems in optical properties may occur.
[0007] Patent Document 2 proposes a polyimide using, as a monomer, a tetracarboxylic acid dianhydride having a specific alicyclic structure or a fluorine-containing tetracarboxylic acid dianhydride and a diamine having a fluorene derivative structure. However, since these tetracarboxylic acid dianhydrides having an alicyclic structure and fluorine-containing tetracarboxylic acid dianhydrides have structures that raise concerns about heat resistance, there is a concern that the optical properties may deteriorate during the manufacturing process of a display device that is exposed to high temperatures.
[0008] Patent Document 3 proposes a polyimide that combines heat resistance and low Rth by applying a diamine monomer containing a fluorene derivative structure called a cardo structure to both the diamine and the acid anhydride. However, the proposed structure impairs mechanical strength, and there is a concern that defects such as cracks in the polyimide layer may occur when the polyimide is applied to a flexible display or the like.
[0009] Patent Document 4 proposes reducing yellowness and birefringence by applying a diamine monomer containing a fluorine-containing structure on the acid anhydride side and a fluorene-derived structure substituted with fluorine on the diamine side. However, the polyimide film described in Patent Document 4 is mainly composed of fluorine-containing tetracarboxylic dianhydride, which has low heat resistance, and has a structure with concerns about heat resistance, so there is a concern that the optical properties will deteriorate during the manufacturing process of the display device, which is exposed to high temperatures. In addition, there is little description about the glass transition temperature and thermal decomposition temperature, so there are concerns about heat resistance. [Prior art documents] [Patent documents]
[0010] [Patent Document 1] JP 2014-25059 A [Patent Document 2] WO2013 / 154141 [Patent Document 3] WO2019 / 188305 [Patent Document 4] JP 2019-143164 A Summary of the Invention [Problem to be solved by the invention]
[0011] Therefore, an object of the present invention is to provide a polyimide, a polyimide film, and a display device using the same that have excellent transparency, high heat resistance, low retardation characteristics in the thickness direction, and mechanical strength that is applicable to flexible displays, which were difficult to achieve with conventional technologies. [Means for solving the problem]
[0012] As a result of intensive research, the present inventors have found that polyimides and polyimide precursors which solve the above-mentioned problems can be obtained by combining, in a prescribed ratio, a specific acid anhydride structure having an ether group (bond) and a diamine monomer containing a fluorene derivative structure known as a cardo structure, and have thus completed the present invention.
[0013] That is, the present invention is as follows. [1] A polyimide precursor having a structural unit A derived from a tetracarboxylic dianhydride and a structural unit B derived from a diamine, 20 to 99 mol % of the structural unit A is a structural unit A1 derived from a structure represented by the following formula A1, [ka] [In formula (A1), R 1 each independently represents a fluorine atom or an alkyl or alkoxy group having 1 to 3 carbon atoms which may be substituted by a fluorine atom, and p and q each independently represent an integer of 0 to 4. 1 to 80 mol % of the structural unit A is a structural unit A2 having a bond dissociation energy of 80 kcal / mol or more; A polyimide precursor, characterized in that 20 to 80 mol % of structural units B are structural units B1 derived from a structure represented by the following formula B1: [ka] [2] 20 to 80 mol % of the structural unit A is the structural unit A1, 2. The polyimide precursor according to claim 1, wherein 20 to 80 mol % of the structural unit A is the structural unit A2. [3] The polyimide precursor according to [1] or [2], wherein the structural unit A2 includes at least one of the following structural units A3 to A5: [ka] [In formula (A5), X represents a single bond or a carbonyl group.] [4] The polyimide precursor according to any one of [1] to [3], wherein 20 to 80 mol % of the structural unit B is a structural unit B2 represented by the following formula B2: [ka] [In formula (B2), R 2 each independently represents a fluorine atom or an alkyl or alkoxy group having 1 to 3 carbon atoms which may be substituted with a fluorine atom, and t and u each independently represent an integer of 0 to 4. In addition, the structural unit B has a fluorine atom in its structure.] [5] The polyimide precursor according to any one of [1] to [4], wherein 30 to 70 mol % of the structural units B are structural units B1. [6] A polyimide obtained by heat-treating the polyimide precursor according to any one of [1] to [5]. [7] A polyimide film, characterized by being obtained by applying the polyimide precursor according to any one of [1] to [5] onto a support, drying the same, and heat-treating the same. [8] A display device comprising the polyimide film according to [7] and a functional layer laminated on the polyimide film. [9] A polyimide film having a structural unit A derived from a tetracarboxylic dianhydride and a structural unit B derived from a diamine, the polyimide film having a glass transition temperature (Tg) of 350° C. or higher as calculated by a thermomechanical analysis (TMA) method, 20 mol % or more of the structural units A are structural units A1 derived from a structure represented by the following formula A1, [ka] [In formula (A1), R 1 each independently represents a fluorine atom or an alkyl or alkoxy group having 1 to 3 carbon atoms which may be substituted by a fluorine atom, and p and q each independently represent an integer of 0 to 4. A polyimide film, characterized in that 20 to 80 mol % of structural units B are structural units B1 derived from a structure represented by the following formula B1: [ka]
[10] The polyimide film according to [9], wherein 20 to 80 mol % of the structural units B are structural units B2 represented by the following formula B2: [ka] [In formula (B2), R 2 each independently represents a fluorine atom or an alkyl or alkoxy group having 1 to 3 carbon atoms which may be substituted with a fluorine atom, and t and u each independently represent an integer of 0 to 4. In addition, the structural unit B has a fluorine atom in its structure.]
[11] The polyimide film according to [9] or
[10] , which satisfies all of the following (a) to (c): (a) Retardation in the thickness direction (Rth10) converted to a thickness of 10 μm is less than 200 nm. (b) 1% thermal weight loss temperature (TD1) is 450°C or higher. (c) Yellowness index (YI) converted to a thickness of 10 μm is 10 or less.
[12] The polyimide film according to any one of [9] to
[11] , wherein the change in YI (ΔYI420) upon heating at 420° C. for 30 minutes is 5 or less.
[13] A display device comprising the polyimide film according to any one of [9] to
[12] and a functional layer laminated thereon. Effect of the Invention
[0014] The polyimide and polyimide film of the present invention have excellent transparency, high heat resistance, and low retardation in the thickness direction. They also have mechanical properties applicable to flexible displays. Furthermore, even when heated at high temperatures, the film does not discolor much, and shows stable optical properties for forming multiple layers during the process. Therefore, they can be suitably used for flexible devices that require transparency, such as substrates for organic EL devices, touch panel substrates, and color filter substrates. For example, they can be suitably used in the process of forming TFT substrates and color filter (CF) substrates for flexible liquid crystal displays (LCDs). Furthermore, they can be suitably used for flexible devices that require extremely high heat resistance, such as the process of forming TFT substrates for flexible organic light-emitting diodes (OLEDs). DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0015] Hereinafter, an embodiment of the present invention will be described.
[0016] <Polyimide film> The polyimide and polyimide film of the present invention can be produced, for example, as follows. First, a tetracarboxylic dianhydride (hereinafter also simply referred to as "acid dianhydride") and a diamine are polymerized in the presence of a solvent to obtain a varnish of a polyimide precursor (also referred to as "polyamic acid"). Next, this varnish is applied to a supporting substrate such as glass and heat-treated to imidize the polyimide, which is then peeled off from the substrate to obtain a polyimide film.
[0017] The type of the support substrate is not limited as long as it has heat resistance sufficient to withstand the heat treatment conditions during imidization, and examples of the substrate that can be used include glass, metal foil (copper foil, stainless steel foil, etc.), and polyimide film. Hereinafter, examples of methods for producing polyimide and polyimide films will be described in detail for each production step.
[0018] <Synthesis of polyimide precursor> First, diamine is dissolved in an organic solvent, and then acid dianhydride is added to the solution, and the solution is reacted at room temperature for about 3 to 96 hours to polymerize these monomers, thereby obtaining a varnish of a polyimide precursor (also called a "polyamic acid solution"). When adding diamine or acid anhydride, heating may be performed at 30 to 50°C for 2 to 10 hours in order to dissolve these monomers more quickly. In addition, aromatic monoamine or aromatic dicarboxylic anhydride may be added before or during the reaction to cap the molecular terminals of the polyimide precursor with aromatic monoamine or aromatic monocarboxylic anhydride.
[0019] Examples of the organic solvent include N,N-dimethylacetamide, N-methyl-2-pyrrolidone, dimethylformamide, n-methylpyrrolidinone, 2-butanone, diglyme, xylene, butyrolactone, and triethylene glycol dimethyl ether. These can be used alone or in combination of two or more kinds.
[0020] From the viewpoint of achieving both coatability and mechanical properties, the molecular weight of the polyimide precursor is preferably adjusted to a range of 80,000 to 800,000 as the weight average molecular weight (Mw). If the molecular weight falls below this range, there is a concern that the mechanical properties may deteriorate, whereas if the molecular weight exceeds this range, there is a concern that gelation may cause the generation of foreign matter during coating.
[0021] The molar ratio of diamine to dianhydride used in the reaction can be adjusted within the range of (diamine / dianhydride) = 0.980 to 1.025. Within this range, the Mw can be easily controlled. In addition, the coating property and mechanical properties are excellent. The above operations may be performed under a nitrogen stream.
[0022] <Application of polyimide precursor varnish and heat treatment> When the obtained polyimide precursor varnish is applied to a support substrate, it is preferable from the viewpoint of coatability to adjust the viscosity of the varnish to the range of 1,000 to 50,000 cps (=cP) by adjusting the concentration and Mw of the polyimide precursor. If the viscosity is high, a solvent may be added to dilute the varnish. In order to prevent uneven thickness during application of the polyimide precursor varnish, the solid content is preferably 5 to 30%, more preferably 7 to 20%, and further preferably 10 to 15%.
[0023] In order to improve adhesion to the substrate, the surface of the supporting substrate to which the polyimide precursor varnish is to be applied may be appropriately surface-treated before coating.
[0024] After the polyamic acid solution is applied, the supporting substrate is heat-treated to imidize the polyamic acid, and a polyimide film is laminated on the supporting substrate to form a polyimide-supporting substrate laminate. When the supporting substrate is glass, the laminate is called a polyimide-glass laminate.
[0025] The conditions of the heat treatment in the imidization step are that the maximum temperature of the heat treatment (hereinafter referred to as the "maximum imidization temperature") is 300 to 450°C. The lower limit of the maximum imidization temperature is more preferably 350°C. The upper limit of the maximum imidization temperature is more preferably 435°C. If the maximum imidization temperature is within this range, a polyimide film can be obtained that has excellent heat resistance and low Rth characteristics in the thickness direction while maintaining excellent transparency, and that has mechanical properties applicable to flexible displays while maintaining low YI even in heat treatment such as a TFT substrate manufacturing process. If the maximum imidization temperature is less than 300°C, a large amount of residual solvent remains in the polyimide film, and there is a concern that the residual solvent will be released during the formation of a display device, causing problems such as peeling. On the other hand, if the maximum temperature exceeds 450°C, the transmittance of the polyimide film in the visible light region decreases and the yellowness index (YI) tends to increase. Furthermore, the mechanical strength tends to deteriorate. The retention time at the maximum temperature is preferably 5 minutes to 3 hours, although it varies depending on the heating method, the heat capacity of the supporting substrate, the thickness of the polyimide film, etc. If it is less than 5 minutes, the effect of the heat treatment at that temperature is small, and if it exceeds 3 hours, especially when the maximum imidization temperature is 400° C. or higher, excessive heat is applied, so that the transmittance in the visible light region decreases and the YI tends to increase.
[0026] In addition, imidization can be performed under any conditions, such as in air, under low oxygen concentration, in an inert gas atmosphere, under reduced pressure, or under vacuum, but from the viewpoint of reducing the YI, it is preferable to perform imidization under an oxygen concentration of 10% or less, more preferably 5% or less, and even more preferably 3% or less. Conditions other than the maximum temperature in the imidization step, such as the rate of temperature rise, can be appropriately adjusted depending on the properties and amount of the organic solvent contained in the polyamic acid solution and the structure of the polyamic acid.
[0027] Prior to imidization, in order to volatilize the organic solvent contained in the polyamic acid solution, drying may be performed for about 2 to 60 minutes at 200° C. or less. For example, the polyamic acid solution is applied onto a supporting substrate using an applicator, pre-dried for 3 to 60 minutes at a temperature of 150° C. or less, and then the above-mentioned heat treatment is performed for removing the solvent and imidization. In order to stabilize the molecular structure rearranged at the maximum temperature, the temperature may be lowered gradually over a period of time when lowering from the maximum temperature to room temperature.
[0028] The coating method may be a known method, but is preferably a spin coating method or a slit coater method.
[0029] In addition, in the heat treatment in the imidization process, a dehydrating agent and a catalyst are added to the polyamic acid solution to cause a reaction, which is called "chemical imidization". In this case, the maximum imidization temperature can be lower than that of a heat treatment that does not use a dehydrating agent and a catalyst, which is called "thermal imidization". In other words, the lower limit of the maximum imidization temperature can be set to 180°C. Here, known dehydrating agents and catalysts can be applied. Examples of dehydrating agents include acetic anhydride, pyridine, 1,4-diazabicyclo[2.2.2]octane, etc. In addition, examples of catalysts include imidazole and 2-methylimidazole, etc. However, in order to solubilize the polyimide, restrictions are placed on the chemical structure, and components that lower Tg, such as a bent structure, are required to be added, so "thermal imidization" is preferred. In the heat treatment in the imidization step, a varnish of the polyimide precursor may be applied to a supporting substrate, and the supporting substrate may be dried at 200° C. or less for about 2 to 60 minutes, and then the resulting dry film of the polyimide precursor may be peeled off from the supporting substrate, and the dry film of the polyimide precursor may be fixed to a SUS frame or the like, and the heat treatment in the imidization step may be performed. However, when the heat treatment is performed by fixing the polyimide precursor to a substrate, it is preferable to apply the polyamic acid solution and then heat treat the supporting substrate together to imidize the polyamic acid, from the viewpoint of achieving a low CTE while exhibiting in-plane isotropy due to the pseudo-stretching effect caused by volume shrinkage.
[0030] <Chemical structures of polyimides and polyimide precursors> The polyimide, polyimide film, and polyimide precursor of the present invention have a structural unit A derived from a specific tetracarboxylic acid anhydride and a structural unit B derived from a specific diamine. The structural unit A represents a tetravalent group derived from a tetracarboxylic acid dianhydride and is also called an acid dianhydride residue. The structural unit B represents a divalent group derived from a diamine and is also called a diamine residue. The details will be explained below.
[0031] <Acid anhydride residue> In the polyimide, polyimide film, and polyimide precursor of the present invention, the structural unit A contains a structural unit derived from a structure represented by the following formula A1 (hereinafter, also referred to as "A1 residue"). [ka] In the above formula (A1), R 1 each independently represents a fluorine atom or an alkyl or alkoxy group having 1 to 3 carbon atoms which may be substituted by a fluorine atom, and p and q each independently represent an integer of 0 to 4. 1 may be the same or different. A1 has a structure in which two phenyl groups are bonded by an ether bond, so when it forms an imide structure with a diamine, the electron-accepting ability of the acid anhydride residue is suppressed, suppressing charge transfer interactions and providing transparency. Furthermore, since it does not contain a weak bonding site, bond decomposition during heating is suppressed, and even when heat treatment is performed, the increase in YI is suppressed, so heat resistance can be expected. R 1 From the viewpoint of the heat resistance, it is preferable that is unsubstituted (hydrogen atom) or a methyl group, and more preferably is a hydrogen atom.
[0032] Specifically, 4,4'-oxydiphthalic anhydride (ODPA) and 3,4'-oxydiphthalic anhydride are preferred acid dianhydrides.
[0033] In order to effectively exert the effect of A1, the structural unit A is designed to have 20 mol % or more, and preferably, from the viewpoint of a high glass transition temperature (Tg), 20 mol % to 99 mol %, more preferably, 20 mol % to 80 mol %, even more preferably, 30 mol % to 70 mol %, and particularly preferably, 40 mol % to 60 mol % of the structural unit A as A1 residues. If the A1 residues are less than 20 mol %, the optical properties and heat resistance may be deteriorated.
[0034] Here, in the present invention, it is preferable that the structural unit A contains a structural unit A2 other than the structural unit A1 residue, all of which have a bond dissociation energy of 80 kal / mol or more. Although a detailed explanation will be given later, if a structural unit having a bond dissociation energy of less than 80 kal / mol is contained in a polyimide, decomposition will begin due to heating during display processing, etc., and the yellowness will deteriorate. Since all structural units in A2 have high bond dissociation energy, the introduction of the corresponding structure into a polyimide is expected to improve the heat resistance of the polyimide. The higher the bond dissociation energy constituting A2, the more preferable it is, and since a combination with a diamine-derived structural unit B2 described later is a prerequisite, it is preferable to select a structure from the viewpoint of increasing heat resistance rather than yellowness.
[0035] Examples of the structural unit A2 include structural units derived from the following acid dianhydrides: pyromellitic dianhydride (PMDA), 3,3',4,4'-biphenyltetracarboxylic dianhydride (BPDA), 2,3,6,7-naphthalenetetracarboxylic dianhydride (NTCDA), 9,9-bis(3,4-dicarboxyphenyl)fluorene dianhydride, 2,3',3,4'-biphenyltetracarboxylic dianhydride, 2,2',3,3'-, 2,3,3',4'- or 3,3',4,4'-benzophenonetetracarboxylic dianhydride, 3,3'',4,4''-, 2,3,3'',4''- or 2,2'',3,3''-p-terphenyltetracarboxylic dianhydride, 1,2,7,8-, 1,2,6,7- Or structural units derived from aromatic tetracarboxylic dianhydrides such as 1,2,9,10-phenanthrene-tetracarboxylic dianhydride, 2,3,6,7-anthracenetetracarboxylic dianhydride, 1,2,5,6-naphthalenetetracarboxylic dianhydride, 1,4,5,8-naphthalenetetracarboxylic dianhydride, 2,3,8,9-, 3,4,9,10-, 4,5,10,11- or 5,6,11,12-perylene-tetracarboxylic dianhydride, pyrazine-2,3,5,6-tetracarboxylic dianhydride, pyrrolidine-2,3,4,5-tetracarboxylic dianhydride, and thiophene-2,3,4,5-tetracarboxylic dianhydride.
[0036] Among these, from the viewpoint of heat resistance, it is preferable that the structural unit A2 contains at least one structure selected from the following structures A3 to A5. [ka] [In formula (A5), X represents a single bond or a carbonyl group.] And, pyromellitic anhydride (PMDA) represented by A3 is more preferable.
[0037] In order to effectively exert the effect of A2, the structural unit A is designed to have 1 mol% or more, preferably 20 mol% to 80 mol%, more preferably 30 mol% to 70 mol%, even more preferably 40 mol% to 70 mol%, and particularly preferably 40 mol% to 60 mol% of the structural unit A as A2 residues. The A2 residues are effective in imparting a high Tg. If the A2 residues exceed 80 mol%, there is a concern that optical properties such as yellowness may deteriorate. By controlling the structural ratio of A1 and A2, the balance between optical properties and heat resistance can be controlled.
[0038] The structural unit A may contain known structural units other than the structural units A1 and A2, each of which has a bond with a bond dissociation energy of less than 80 kal / mol, in an amount of preferably 10 mol % or less, more preferably 5 mol % or less, and even more preferably 3 mol % or less of the structural unit A, to the extent that the heat resistance of the polyimide film of the present invention and the YI change (ΔYI420) when heated at 420° C. are not impaired. Most preferably, the structural unit A does not contain such known structural units.
[0039] <Diamine residue> In the polyimide film and polyimide precursor of the present invention, the structural unit B contains a structural unit derived from a structure represented by the following formula B1 (hereinafter also referred to as a "B1 residue"). [ka] More preferably, the B1 residue contains a structural unit derived from a structure represented by the following formula B1-1. [ka]
[0040] Since B1 has a cardo structure in the molecule, it is sometimes referred to as a cardo structure-containing diamine. Since it is mainly composed of an aromatic skeleton, it has excellent heat resistance, and since it has a conformation in which the fluorene skeleton part and the benzene substituted with the diamine are perpendicular to each other, it is expected to have the effect of reducing Rth, which is the phase difference in the thickness direction. In other words, it is expected to have both heat resistance and a low Rth in the thickness direction. Furthermore, since the benzene ring substituted with the amino group is substituted with fluorine, it is possible to suppress the charge transfer transition with the acid anhydride-derived structure. Therefore, it is possible to expect high heat resistance like A2, but even if a structure that is concerned about deterioration of the yellowness index (YI) is introduced, it is possible to suppress the increase in YI. In other words, by substituting fluorine, it is possible to introduce a high heat resistant structure on the acid anhydride side, and the heat resistance of the polyimide can be improved.
[0041] In order to effectively exert the effect of B1, the structural unit B is designed to have 20 to 80 mol %, preferably 30 to 70 mol %, and more preferably 40 to 60 mol % of the B1 residue. If the B1 residue is less than 20 mol %, Rth becomes high. On the other hand, if it exceeds 80 mol %, the proportion of the cardo structure becomes high, making the polyimide film brittle and deteriorating the mechanical properties. From the viewpoint of the mechanical properties of the polyimide film, when the total of the structural unit A and the structural unit B is taken as 100 mol %, the B1 residue is preferably less than 50 mol %, more preferably less than 40 mol %, and even more preferably less than 30 mol %.
[0042] In addition, the structural unit B preferably contains a structural unit derived from a structure represented by the following formula B2, in addition to the B1 residue. [ka] In formula (B2), R 2 each independently represents a fluorine atom or an alkyl or alkoxy group having 1 to 3 carbon atoms which may be substituted with a fluorine atom, and t and u each independently represent an integer of 0 to 4. The structural unit B has a fluorine atom in its structure. 2 may be the same or different.
[0043] Diamines with a fluorine-containing biphenyl structure represented by chemical formula (B2) (hereinafter referred to as "diamine (2)") have excellent heat resistance because they are mainly composed of an aromatic skeleton, and the fluorine-containing structure also gives them excellent transparency. Furthermore, they are expected to have the effect of promoting the mechanical strength of the film by providing an appropriate molecular orientation. 2 From the viewpoint of the heat resistance, is preferably a fluorine atom or a fluorine atom-substituted methyl group.
[0044] Specific examples include structural units derived from the following formulas (B2-1) to (B2-4). [ka]
[0045] Among the above formulas (B2-1) to (B2-4), formula (B2-1) which is a structural unit derived from 2,2'-bis(trifluoromethyl)-4,4'-diaminobiphenyl (TFMB) is more preferred.
[0046] In order to effectively exert the effect of B2, the structural unit B is designed to be 20 to 80 mol %, preferably 30 to 70 mol %, and more preferably 40 to 60 mol % of the B2 residue. If the B2 residue is less than 20 mol %, the proportion of the cardo structure becomes high, which deteriorates the mechanical properties. On the other hand, if it exceeds 80 mol %, the proportion of the cardo structure becomes small, which increases Rth.
[0047] Other diamines may be used in combination as long as they do not impair the effects of the present invention. The structural unit B may contain structural units other than B1 and B2 residues (hereinafter referred to as "other diamine residues") in a range of 50 mol % or less, preferably 30 mol % or less. However, from the viewpoint of heat resistance, it is preferable that the other diamine residues have a chemical structure in which the bond dissociation energy is 80 kal / mol or more. Other diamine residues include, for example, 2,2'-dimethyl-4,4'-diaminobiphenyl (m-TB), 2,2'-divinyl-4,4'-diaminobiphenyl (VAB), 4,4'-diaminobiphenyl, p-phenylenediamine (p-PDA), m-phenylenediamine (m-PDA), 3,4'-diaminobenzophenone, (3,3'-bisamino)diphenylamine, 1,4-bis(3-aminophenoxy)benzene, 1,3-bis(4-aminophenoxy)benzene (TPE-R), 3-[4-(4-aminophenoxy)phenoxy]benzene, and the like. Examples of structural units derived from benzeneamine, 3-[3-(4-aminophenoxy)phenoxy]benzeneamine, 1,3-bis(3-aminophenoxy)benzene (APB), bis[4-(3-aminophenoxy)phenyl]ether, bis[4-(3-aminophenoxy)]benzophenone, bis[4-(4-aminophenoxy)phenyl]ether (BAPE), bis[4-(4-aminophenoxy)phenyl]ketone (BAPK), bis[4-(3-aminophenoxy)]biphenyl, bis[4-(4-aminophenoxy)]biphenyl, and the like.
[0048] In the polyimide, polyimide film, and polyimide precursor of the present invention, optical properties such as YI and Rth, heat resistance such as glass transition temperature (Tg), mechanical strength, and the like can be controlled by designing the types and molar ratios of the acid dianhydrides and diamines.
[0049] <Polyimide film thickness> In the polyimide film of the present invention, the average thickness is preferably 5 μm or more and 50 μm or less. A more preferable lower limit is 7 μm. On the other hand, a more preferable upper limit is 30 μm, and even more preferably 15 μm. The average thickness may be measured, for example, according to the method described below. If the thickness is less than 5 μm, the mechanical strength of the polyimide film decreases, and there is a concern of defects such as breakage during processing. If the thickness exceeds 50 μm, the optical properties such as YI and Rth deteriorate.
[0050] <1% thermogravimetric reduction temperature TD1> In addition, the polyimide film of the present invention has an advantage that it is excellent in heat resistance and is difficult to decompose even when heat treated at 350°C or higher in the manufacturing process of a TFT substrate for flexible OLED, a TFT substrate for flexible LCD, and a CF substrate by optimizing the type, molar ratio, Mw, etc. of the monomer. As an index of this difficulty in decomposition, the 1% thermal weight loss temperature (TD1) can be mentioned. It can be said that the higher the TD1, the less likely the weight loss due to the decomposition of the film occurs even in a high-temperature heat treatment. Conversely, it can be said that the lower the TD1, the more likely the weight loss due to the decomposition of the film occurs due to a high-temperature heat treatment. There is a concern that the generation of decomposition products of the film may cause problems such as peeling of the substrate in the above manufacturing process. The polyimide film of the present invention has a TD1 of 450°C or higher. Preferably, the TD1 is 500°C or higher, more preferably 515°C or higher.
[0051] In addition to the decomposition of the film, the heat treatment also releases volatile components, including residual solvents, from the film. The 1% thermal weight loss in the TD1 value includes the weight loss due to the release of these volatile components. Naturally, if the release of volatile components is large, there is concern about defects such as peeling of the substrate in the manufacturing process. Therefore, in order to make TD1 450°C or higher, in addition to the heat resistance of the film itself, it is also important to control the volatile components contained in the film. As an index of the amount of volatile components, the weight loss difference using TG-DTA can be mentioned. Specifically, in the present invention, the weight loss ratio ΔTG (300-100) was measured under a nitrogen atmosphere at a temperature rise of 10°C / min, calculated from the weight difference between 100°C and 300°C based on the weight of the polyimide film at 100°C. Under these conditions, the amount of volatile components (mainly the amount of residual solvent and low molecular weight components) released at a relatively low temperature where the film is less likely to decompose can be measured. For the reason of suppressing defects such as peeling of the substrate during the above steps, ΔTG(300−100) is preferably less than 5%, more preferably less than 3%, and even more preferably less than 1%.
[0052] <Thickness retardation Rth> In addition, the polyimide film of the present invention has an advantage that the retardation Rth in the thickness direction is 200 nm or less by optimizing the type of monomer, molar ratio, Mw, etc., and therefore, even if it is applied to a bottom emission type substrate, problems such as external light reflection can be suppressed. The preferred range of Rth is 200 nm or less, more preferably 100 nm or less, and even more preferably 80 nm or less. By keeping it within the above range, it can also be applied to a bottom emission type substrate.
[0053] <Glass transition temperature Tg> In addition, the polyimide film of the present invention has an advantage that the polyimide film is unlikely to deteriorate or undergo dimensional changes even when heat treatment is performed in the manufacturing process of a TFT substrate for flexible OLED use, a TFT substrate for flexible LCD use, or a CF substrate, because the glass transition temperature Tg is 350°C or higher by optimizing the type, molar ratio, Mw, etc. of the monomer. The glass transition temperature Tg is preferably 370°C or higher, more preferably 380°C or higher, and even more preferably 400°C or higher. By keeping it within the above range, defects caused by deterioration, dimensional changes, etc. when heated during the manufacturing process can be suppressed.
[0054] <Yellowness (YI)> In addition, the polyimide film of the present invention has a YI of 10 or less by optimizing the type, molar ratio, Mw, etc. of the monomer, and can be suitably used for substrates that require transparency and little coloring, such as TFT substrates for organic EL devices, touch panel substrates, and color filter substrates. The YI is preferably 10 or less, more preferably 8 or less, and even more preferably 7 or less. By setting the YI in this range, the visibility of the substrate is improved. It is preferable that the YI satisfies the above range when converted into a film thickness of 10 μm.
[0055] <ΔYI> In addition, by optimizing the type of monomer, molar ratio, Mw, etc., the polyimide film of the present invention has a change in yellowness (hereinafter referred to as ΔYI420) of 5 or less even after heating at 420°C for 30 minutes. Therefore, even if heat treatment at 400°C or higher is performed in the manufacturing process of TFT substrates for flexible OLEDs, TFT substrates for flexible LCDs, and CF substrates, the polyimide film has the advantage of being less discolored. As above, the ΔYI after this heat treatment is calculated as the YI converted to a film thickness of 10 μm. ΔYI420 is preferably from 0 to 5, and more preferably from 0 to 3.5. If it can be kept within the above range, transparency can be maintained even when heated at the manufacturing process temperature.
[0056] <Tensile elongation> The polyimide film of the present invention has a tensile elongation of 5% or more by optimizing the type, molar ratio, Mw, etc. of the monomer, so that it does not break during the manufacturing process, and has excellent foldability when used as a flexible display. Since it has such a tensile elongation, for example, after a functional layer such as a display element is formed on the surface of the polyimide film, the polyimide film can be peeled off cleanly from the glass (supporting substrate) without breaking, which is preferable. More preferably, the tensile elongation is 10% or more.
[0057] <Coefficient of Thermal Expansion (CTE)> The polyimide film of the present invention has a CTE of less than 100 ppm / K and a sufficiently high Tg by optimizing the type of monomer, molar ratio, Mw, etc., and can therefore be suitably used for applications such as relatively large displays such as televisions and signage. From this viewpoint, the CTE is preferably less than 100 ppm / K, more preferably 80 ppm / K or less, and even more preferably 70 ppm / K or less. There is no particular restriction on the lower limit, but from the viewpoint of dimensional stability, 0 ppm / K or more is preferable.
[0058] <Bond dissociation energy> In the present invention, as described above, the structural unit A2 in particular is composed of a structure (bond) with a bond dissociation energy of 80 kcal / mol or more, and therefore the entire molecular structure satisfies the bond dissociation energy. Here, the bond dissociation energy in a chemical structure is the energy required to cleave a specific bond in a molecule, and when a molecule is represented by R1-R2, it is given as the enthalpy change of the dissociation reaction represented by the following formula X. R1-R2 → R1 + R2...(Formula X) In this case, the specific value of the bond dissociation energy can be known from known documents, etc. In this application, the following documents are referred to, but are not limited to these. Reference 1: Chemistry Handbook, Revised 3rd Edition II - Page 324 Reference 2: Polymer Papers, vol.42, No.7, pp.443-451 (July, 1985) Reference 3: Masaya Kurata (ed.), ''Nonmetals Challenging the Ideal'', Chapter 2 Heat-Resistant Materials, Industrial Research Institute (1981).
[0059] The bond dissociation energies of typical acid anhydride monomers used in polyimides can be summarized as follows, with reference to similar bonds in the literature. The bond dissociation energy values shown below indicate the energy required to dissociate the bonds in the dashed lines, and are the bond dissociation energy values of the "bonds referenced in the literature." That is, for PMDA, the bond dissociation energy of the imide bond is used, and for the rest, the bond dissociation energy of the non-imide bond with the lowest bond dissociation energy in the structure is used. [ka]
[0060] As mentioned above, PMDA, BPDA, BTDA, and ODPA are composed of bond dissociation energies equal to or greater than that of the imide bond (89 kcal / mol), so their introduction into the structure is thought to have little effect on the deterioration of heat resistance. On the other hand, there are concerns that 6FDA and H-PMDA may deteriorate their heat resistance because they contain bonds with low bond dissociation energies in the molecule. In fact, in Comparative Example 5 described later, heating was performed at 420°C simulating a TFT manufacturing process, and changes in YI were examined, and the deterioration of YI was significant in structures containing 6FDA. Therefore, in the present invention, it is necessary to configure a chemical structure with a bond dissociation energy of at least 72 kcal / mol or more, which is at least 6FDA, and it is preferable not to contain an alicyclic structure such as H-PMDA, which has poor heat resistance. From the above perspective, the bond dissociation energy of the bond contained in the bond is preferably 80 kcal / mol or more, more preferably 85 kcal / mol or more, and more preferably 89 kcal / mol or more.
[0061] In the polyimide of the present invention, 0.1 to 5 mole units of a crosslinking component may be added to the composition in order to improve heat resistance.
[0062] The polyimide film of the present invention may be made of multiple polyimide layers. In the case of a single layer, as described above, it is preferable that the average thickness is 5 to 50 μm. In the present invention, the average thickness means a value obtained by measuring the thickness at intervals of 5 cm in each of the vertical and horizontal directions in the plane with a dial gauge or a micrometer and averaging the measured thickness. On the other hand, in the case of multiple layers, it is sufficient that the main polyimide layer is a polyimide film having the above-mentioned thickness. Here, the main polyimide layer refers to the polyimide layer that has the largest thickness ratio among the multiple polyimide layers, and its average thickness is preferably 5 to 50 μm.
[0063] <Transparent polyimide substrates for flexible devices> The transparent polyimide substrate for flexible devices using the polyimide film of the present invention can be obtained, for example, by using a glass substrate as a supporting substrate, forming a polyimide film on the supporting substrate, then laminating a functional layer on the transparent polyimide film, and peeling off the supporting substrate. The type of functional layer laminated on the polyimide film is not particularly limited, but includes display devices such as liquid crystal display devices, organic EL display devices, and electronic paper, as well as components of display devices such as color filters. In addition, various functional devices used in conjunction with the display devices, including organic EL lighting devices, touch panel devices, conductive films laminated with ITO, etc., gas barrier films that prevent the penetration of moisture, oxygen, etc., and components of flexible circuit boards, are also included. That is, the display element referred to in the present invention includes not only components such as liquid crystal display devices, organic EL display devices, and color filters, but also includes one or a combination of two or more of organic EL lighting devices, touch panel devices, electrode layers or light-emitting layers of organic EL display devices, gas barrier films, adhesive films, TFTs, wiring layers or transparent conductive layers of liquid crystal display devices, etc.
[0064] As a method for peeling off the supporting substrate, in the case of the polyimide film of the present invention, the supporting substrate can be easily peeled off by a known method, such as by irradiating the interface between the supporting substrate (glass) and the polyimide film with laser light to peel it off, or by making an incision in the film and peeling it off.
[0065] In addition, the forming conditions of the functional layer are appropriately set according to the target flexible device, but generally, after forming a metal film, an inorganic film, an organic film, etc. on a polyimide film, it can be obtained by using a known method such as patterning into a predetermined shape or heat treatment as necessary. That is, the means for forming these display elements are not particularly limited, and for example, sputtering, deposition, CVD, printing, exposure, immersion, etc. are appropriately selected, and these process treatments may be performed in a vacuum chamber, etc., if necessary. After forming the functional layer on the polyimide film, the support substrate may be peeled off immediately after forming the functional layer through various process treatments, or it may be peeled off immediately before using it as a display device after a certain period of time has passed and the functional layer is integrated with the support substrate.
[0066] An example of a polyimide film with a functional layer in which an organic EL display element is attached as a functional layer on the polyimide film of the present invention is shown. First, a gas barrier layer is provided on the polyimide film of the present invention so as to prevent the permeation of moisture and oxygen. Next, a circuit configuration layer including a TFT is formed on the upper surface of the gas barrier layer. In an organic EL display device, a LTPS-TFT having a high operating speed is mainly selected as the TFT. In this circuit configuration layer, an anode electrode made of a transparent conductive film of, for example, ITO (Indium Tin Oxide) is formed for each of a plurality of pixel regions arranged in a matrix on the upper surface of the circuit configuration layer. Furthermore, an organic EL light-emitting layer is formed on the upper surface of the anode electrode, and a cathode electrode is formed on the upper surface of the light-emitting layer. This cathode electrode is formed in common for each pixel region. Then, a gas barrier layer is formed again so as to cover the surface of this cathode electrode, and a sealing substrate is further installed on the outermost surface for surface protection. It is desirable from the viewpoint of reliability to laminate a gas barrier layer that prevents the permeation of moisture and oxygen on the surface of the sealing substrate on the cathode electrode side. The organic EL light-emitting layer is formed from a multilayer film (anode electrode - light-emitting layer - cathode electrode) consisting of a hole injection layer - hole transport layer - light-emitting layer - electron transport layer, etc.; however, since the organic EL light-emitting layer deteriorates due to moisture and oxygen, it is generally formed by vacuum deposition and is continuously formed in a vacuum, including the formation of the electrodes.
[0067] Also, an example of a polyimide film with a functional layer, in which a projected capacitive coupling type touch panel is attached onto the polyimide film of the present invention, is shown. Two electrode rows (first and second electrodes) are provided vertically and horizontally on the polyimide film of the present invention, and the change in capacitance of the electrodes is measured when a finger touches the screen, allowing precise detection of the touch position. A specific structure is a first substrate on which the first electrode is formed and a second substrate on which the second electrode is formed, joined together via an insulating layer (dielectric layer). Thinner, lighter, and more flexible devices can be achieved by replacing the substrate on which the electrodes are formed with a flexible resin substrate instead of the conventional glass substrate. Further thinner and lighter devices are also being developed by forming the first and second electrodes on a single substrate.
[0068] In addition, since the display device using the polyimide film of the present invention as a substrate is transparent and bendable, it can also be applied to, for example, a display device substrate of a rollable television (in this case, the functional layer corresponds to an organic EL element) and a see-through display substrate in the display part of a mobile device (a display substrate of a display in an under-display camera structure in which a camera is provided under the see-through display. In this case, the functional layer corresponds to an organic EL element). In particular, in the display device substrate of a rollable television, since the polyimide film of the present invention also has a low Rth, it can be suitably used in the case of a bottom emission type structure that is advantageous for large size. EXAMPLES
[0069] The present invention will be specifically described below based on examples and comparative examples, but the present invention is not limited to these examples.
[0070] The abbreviations of the raw materials used in the examples are shown below. (Diamine) TFMB: 2,2'-bis(trifluoromethyl)-4,4'-diaminobiphenyl BAFL: 9,9-bis(4-aminophenyl)fluorene BOFAF: 9,9-di(3-fluoro-4-aminophenyl)fluorene (acid dianhydride) PMDA: Pyromellitic dianhydride ODPA: 4,4'-oxydiphthalic dianhydride 6FDA: 2,2'-bis(3,4-dicarboxyphenyl)hexafluoropropane dianhydride (solvent) ·NMP: N-methyl-2-pyrrolidone
[0071] The weakest bonds among the bond dissociation energies of the structures derived from various monomers in the present examples and their bond dissociation energy values are as follows: That is, as described above, the bond dissociation energy values shown below indicate the energy required to dissociate the bonds in the dashed lines, and indicate the bond dissociation energy values of the "bonds referred to in the literature" themselves. [ka]
[0072] The methods for measuring and evaluating the various physical properties in the examples are shown below.
[0073] Coefficient of Thermal Expansion (CTE) A polyimide film measuring 3 mm x 15 mm was heated from 30°C to 450°C at a constant heating rate (10°C / min) while applying a load of 30 mN in a thermomechanical analysis (TMA / SS6100) device, and then cooled from 450°C to 30°C at a constant heating rate (10°C / min). The thermal expansion coefficient was measured from the elongation (linear expansion) of the polyimide film during cooling (from 350°C to 100°C).
[0074] [Yellowness YI〔YI(10)〕] Polyimide films (50 mm x 50 mm) were measured using a SHIMADZU UV-3600 spectrophotometer, and the YI (yellowness index) was calculated based on the following formula (I). The YI was measured at room temperature (23°C). The same applies to the YI after heating. YI=100×(1.2879X-1.0592Z) / Y (I) X, Y, and Z are the tristimulus values of the test piece and are specified in JIS Z 8722. The yellowness index (YI(10)) calculated based on a film thickness of 10 μm and represented by the following formula (II) is calculated using the YI in the above formula (I). YI(10)=YI*10 / thickness (II)
[0075] [Tensile elongation] Test pieces of polyimide film (10 mm × 15 mm) were prepared, and tensile tests were performed in accordance with IPC-TM-650, 2.4.19 at a tensile speed of 10 mm / min using a Tensilon universal testing machine (ORIENTEC Co., Ltd., RTA-250), and the elastic modulus, tensile elongation, and tensile strength were calculated.
[0076] [Glass transition temperature (Tg)] A polyimide film measuring 3 mm x 15 mm was heated from 30°C to 450°C at a constant heating rate (10°C / min) while applying a load of 30 mN in a thermomechanical analysis (TMA / SS6100) device, and then cooled from 450°C to 30°C at a constant heating rate (10°C / min). The glass transition temperature was calculated from the TMA and temperature inflection point during heating.
[0077] [Thickness retardation; Rth(10)] The incidence angle dependence of the retardation of the polyimide film (50mm x 50mm) was measured at a wavelength of 543nm using a birefringence / phase difference evaluation device (Photonic Lattice Co., Ltd., WPA-100) equipped with a rotating device for rotating the sample to change the incident angle of light incident on the sample. The measured values were subjected to numerical analysis of the measurement data of the incidence angle dependence of the retardation to determine the retardation Rth in the thickness direction. The obtained retardation Rth was converted into retardation [Rth(10)] for a film thickness of 10 μm according to the following formula (III). Rth(10)=Rth*10 / thickness (III)
[0078] [1% weight loss temperature (TD1) and weight loss ratio ΔTG(300-100)] A polyimide film weighing 10 to 20 mg was heated from 30°C to 550°C at a rate of 10°C / min in a nitrogen atmosphere using a Hitachi High-Tech Science differential thermal thermogravimetry device TG / DTA6200, and the weight change was measured. The weight at 200°C was set to zero, and the temperature at which the weight loss rate was 1% was defined as the thermal decomposition temperature (TD1). Furthermore, the weight loss ratio calculated from the weight loss from 100°C to 300°C [100 x (weight at 100°C - weight at 300°C) / weight at 100°C] was defined as ΔTG(300-100) based on the weight at 100°C.
[0079] [Viscosity cP] The viscosity was measured at 25° C. using an E-type viscometer (manufactured by Brookfield, product name: DV-II+Pro). The rotation speed was set so that the torque was 10% to 90%, and the value was read when the viscosity stabilized 2 minutes after the start of the measurement.
[0080] Polyimide precursor solutions A to G were prepared according to the following synthesis examples.
[0081] Synthesis Example 1 Under a nitrogen gas flow, in a 200 ml separable flask, diamine was dissolved in NMP according to the composition in Table 1, and then acid dianhydride was added. The solution was stirred at 25°C for 72 hours to carry out a polymerization reaction, and a polyimide (PI) precursor solution A (viscous solution) with a viscosity of 4200 cP was obtained.
[0082] Synthesis Examples 2-7 Similarly to Synthesis Example 1, Synthesis Examples 2 to 7 were carried out according to the compositions in Table 1 to obtain polyimide (PI) precursor solutions B to G (viscous solutions). The viscosities of the various PI precursors are as shown in Table 1.
[0083] [Table 1]
[0084] [Table 2]
[0085] [Example 1] The polyimide precursor solution A obtained in Synthesis Example 1 was applied to a glass substrate (Corning Eagle XG, size = 150 mm × 150 mm, thickness = 0.5 mm) using a spin coater so that the polyimide thickness after curing was about 10 μm. Then, heating was performed at 100 ° C. for 15 minutes. Then, as shown in Table 2, in a nitrogen atmosphere (oxygen concentration: 3% or less), the temperature was raised from room temperature to 435 ° C. at a constant heating rate (4 ° C. / min), and then the temperature was held at 420 ° C. ± 10 ° C. for 30 minutes, and returned to room temperature over 4 hours or more to form a 150 mm × 150 mm polyimide layer (corresponding to polyimide film A-1F) on the glass substrate, and a polyimide laminate A-1 was obtained. The maximum imidization temperature and the holding temperature for 30 minutes shown in Table 2 are values measured by measuring the temperature of the film itself. The same applies to other examples and comparative examples.
[0086] [Comparative Examples 1 to 6] The same procedure as in Example 1 was repeated except that the polyimide precursor solution A was replaced with any one of the polyimide precursor solutions B to G. The imidization temperature was increased to the maximum imidization temperature shown in Table 2, and the temperature was then maintained for 30 minutes at a temperature range 15°C lower than the maximum imidization temperature, to obtain polyimide laminates B-2 to G-7, respectively.
[0087] The laminates obtained in the above Examples and Comparative Examples were cut with a cutter along the periphery of the upper polyimide layer, immersed in water for 30 minutes, removed, wiped off the moisture, and peeled off from the glass with tweezers to obtain polyimide films A-1F to G-7F. The thicknesses of these films are shown in the thickness section of Table 2. The polyimide film D-4F was brittle, and no film suitable for various evaluations was obtained.
[0088] The obtained polyimide films A-1F to C-3F and E-5F to G-7F were evaluated for various properties such as CTE, YI, tensile strength, tensile elongation, elastic modulus, Tg, Rth, TD1, etc. The results are shown in Table 2.
[0089] The obtained polyimide glass laminates A-1 to C-3 and E-5 to G-7 were heated to 420°C in a nitrogen atmosphere at a heating rate of 6°C / min, then held at 420°C for 30 minutes, and then cooled to room temperature and removed. As in the above, only the polyimide layer was cut along the outer periphery of the part to be peeled off with a cutter, immersed in water for 30 minutes, removed, wiped off the moisture, and peeled off from the glass with tweezers to obtain a polyimide film. The YI was measured, and the results are shown in Table 2.
[0090] As shown in Example 1 of Table 2, polyimide combining ODPA with a structure that ensures high heat resistance, such as BOFAF and PMDA, achieves both high heat resistance and low Rth in the thickness direction, and also ensures optical properties such as YI and mechanical strength applicable to flexible displays. Therefore, polyimide-glass laminates using such polyimides can be suitably used not only in display devices such as organic electroluminescence displays, organic electroluminescence lighting, electronic paper, and touch panels, but also as a supporting substrate for forming deposition masks and fan-out wafer level packages (FOWLPs). On the other hand, when only BAFL without fluorine substituents is used as a diamine having a cardo structure, the YI increases and transparency becomes insufficient, making it unsuitable for application to flexible displays, as shown in Comparative Example 1. When BAFL is used without BOFAF as shown in Comparative Example 4, the structure that ensures high heat resistance, such as PMDA, has an upper limit of about 10% from the viewpoint of transparency, so BOFAF containing fluorine substituents is required to ensure heat resistance, transparency, and low Rth. Furthermore, as shown in Comparative Example 2 in Table 2, a composition that does not contain a diamine having a cardo structure has insufficient heat resistance, and as shown in Comparative Example 3, a composition that contains an excessively large proportion of cardo structures has insufficient mechanical strength and is unsuitable for application to flexible displays. Furthermore, as shown in Comparative Example 5 in Table 2, when a chemical structure with a bond dissociation energy of less than 80 kcal / mol such as 6FDA is used, the heat resistance becomes insufficient, and in terms of physical properties, ΔYI when heated to 420°C becomes large, and there is concern that defects such as discoloration may occur during the manufacturing process of flexible displays. In Comparative Example 5 and Comparative Example 6, the Tg is at the same level and the TD1 is also over 500°C, but there is a significant difference in ΔYI, and it can be considered that the effect of chemical structure on ΔYI is large. In order to suppress ΔYI, it is necessary to apply a chemical structure such as ODPA, which is composed of bond dissociation energies of 80 kcal / mol or more.
Claims
1. A polyimide precursor having a structural unit A derived from a tetracarboxylic dianhydride and a structural unit B derived from a diamine, 20 to 99 mol % of the structural unit A is a structural unit A1 derived from a structure represented by the following formula A1, 【Chemistry 1】 [In formula (A1), R 1 each independently represents a fluorine atom or an alkyl or alkoxy group having 1 to 3 carbon atoms which may be substituted by a fluorine atom, and p and q each independently represent an integer of 0 to 4. 1 to 80 mol % of the structural unit A is a structural unit A2 having a bond dissociation energy of 80 kcal / mol or more, 20 to 80 mol % of the structural unit B is a structural unit B1 derived from a structure represented by the following formula B1, A polyimide precursor characterized in that 20 to 80 mol % of the structural unit B is a structural unit B2 represented by the following formula B2: 【Chemistry 2】 【Chemistry 3】 [In formula (B2), R 2 independently represents a fluorine atom or an alkyl or alkoxy group having 1 to 3 carbon atoms which may be substituted with a fluorine atom, and t and u independently represent an integer of 0 to 4. In addition, the structural unit B has a fluorine atom in its structure.]
2. 20 to 80 mol % of the structural unit A is the structural unit A1; 2. The polyimide precursor according to claim 1, wherein 20 to 80 mol % of the structural unit A is the structural unit A2.
3. The polyimide precursor according to claim 1 or 2, wherein the structural unit A2 comprises at least one of the following structural units A3 to A5: 【Chemistry 4】 [In formula (A5), X represents a single bond or a carbonyl group.]
4. The polyimide precursor according to any one of claims 1 to 3, wherein 30 to 70 mol % of the structural unit B is the structural unit B1.
5. A polyimide obtained by heat-treating the polyimide precursor according to any one of claims 1 to 4.
6. 5. A polyimide film obtained by applying the polyimide precursor according to claim 1 onto a support, drying the same and subjecting the same to a heat treatment.
7. A display device comprising the polyimide film according to claim 6 and a functional layer laminated on the polyimide film.
8. A polyimide film having a structural unit A derived from a tetracarboxylic dianhydride and a structural unit B derived from a diamine, the polyimide film having a glass transition temperature (Tg) of 350° C. or higher as calculated by a thermomechanical analysis (TMA) method, 20 mol % or more of the structural unit A is a structural unit A1 derived from a structure represented by the following formula A1, 【Chemistry 5】 [In formula (A1), R 1 each independently represents a fluorine atom or an alkyl or alkoxy group having 1 to 3 carbon atoms which may be substituted by a fluorine atom, and p and q each independently represent an integer of 0 to 4. 20 to 80 mol % of the structural unit B is a structural unit B1 derived from a structure represented by the following formula B1, A polyimide film, characterized in that 20 to 80 mol % of the structural unit B is a structural unit B2 represented by the following formula B2: 【Chemistry 6】 【Chemistry 7】 [In formula (B2), R 2 independently represents a fluorine atom or an alkyl or alkoxy group having 1 to 3 carbon atoms which may be substituted with a fluorine atom, and t and u independently represent an integer of 0 to 4. In addition, the structural unit B has a fluorine atom in its structure.]
9. The polyimide film according to claim 8, which satisfies all of the following (a) to (c): (a) The retardation in the thickness direction (Rth10) converted to a thickness of 10 μm is less than 200 nm. (b) 1% thermal weight loss temperature (TD1) is 450°C or higher. (c) The yellowness index (YI) converted to a thickness of 10 μm is 10 or less.
10. 10. The polyimide film according to claim 8, wherein a change in YI (ΔYI420) upon heating at 420° C. for 30 minutes is 5 or less.
11. A display device comprising the polyimide film according to any one of claims 8 to 10 and a functional layer laminated thereon.
Citation Information
Patent Citations
Humidity sensing material and preparation method and application thereof
CN110330644A
Polyimide rein and polyimide resin film
JP2007091828A
Laminate, and utilization thereof
JP2012040836A
Polyimide film for supporting base material of display device, laminate of the same and method for manufacturing the same
JP2014025059A
Polyimide precursor and resin composition including the same, polyimide film and method for manufacturing the same, and laminate and method for manufacturing the same
JP2014070139A